The Relationship between Role of Drug Supervisor (PMO) with Successful Treatment of Pulmonary Tuberculosis Patients in Working Area Sukamerindu Public Health Center Bengkulu - Suryani Suryani; S. Effendi; Refin Herizon (Sekolah Tinggi Ilmu Kesehatan Tri Mandiri Sakti Bengkulu, 2018)
The impact and dangers of Pulmonary Tuberculosis incidence is causing death. In Bengkulu province in 2011 there were 1.565 cases of pulmonary tuberculosis in 2012 there were 1,670 cases of pulmonary tuberculosis in 2013 there were 2.671 cases of pulmonary tuberculosis and in 2014 there were 2.014 cases of pulmonary tuberculosis this showed that pulmonary tuberculosis was still high. The purpose of this study was to study the relationship of PMO role with the success of the treatment of pulmonary tuberculosis patients in working area of Sukamerindu Public Health Center Bengkulu. The type of research used was an analytic survey, with Cross Sectional research design. Population in this research was all patient of pulmonary tuberculosis in working area of Sukamerindu Public Health Center Bengkulu which had treatment 5 months amounted to 36 people in 2015. Samples taken by using total sampling which amounted to 36 people. Data analysis was done by univariate and bivariate analysis using uni Chi-Square (χ2). The results of this study were 41 patients with pulmonary tuberculosis, 20 people (55.6%) had good role of PMO, and there were 30 people (83.3%) who had successful treatment, there was a significant relationship between the role of PMO with successful treatment of patients with pulmonary tuberculosis with moderate category. It was suggested to the related institution to improve and supervise the cadre of (PMO) so that the success of the treatment of pulmonary tuberculosis will increasing. Keywords : drug supervisor (PMO), successful treatment, pulmonary tuberculosis patients